Investigating Economic Factors of Sustainability in European Smart Cities - Vodă, Ana Iolanda; Radu, Laura-Diana (European Journal of Sustainable Development, 2018)
Smart city is a complex system which faces multiple challenges to support a sustainable socio-economic development and improving the quality of living. Building smart cities is a challenge and an imperative solution for optimizing resources availability and distribution processes in the context of massive urbanization. Although, many aspects shape the development of smart cities, the study aims to examine the importance of research and development (R&D) investments, the patent applications, employed information and communication technology (ICT) specialists, gross domestic product (GDP) and poverty reduction in making cities „smart?. According to our research objective and developed hypothesis, several data analysis have been used: Principal Component Analysis (PCA), Pearson correlation coefficient and Hierarchical clustering tested on 26 European Member states. Our results show that all the above elements are imperative in supporting a long-term city growth and development. Keywords: Smart Cities, Patent Applications, Employed ICT Specialists, R&D Investments, GDP, Poverty Rate